Homelessness—'It will crumble men': The views of staff and service users about facilitating the identification and support of people with an intellectual disability in homeless services. (14th April 2019) - McKenzie, Karen; Murray, George; Wilson, Helen; Delahunty, Lauren
Abstract: People with an intellectual disability (ID) face significant health inequalities and barriers to accessing appropriate support, which are made worse if the person is also homeless. An important barrier is that services may not recognise that the person has ID. This qualitative study explored the views of staff members and service users about the identification and support needs of homeless people with ID and the role of an ID screening questionnaire as a way to help improve service provision. Semi‐structured interviews were conducted with 16 staff members and 8 service users from homeless services in the South East of Scotland between March 2017 and 2018. Thematic analysis identified four themes: 'not diagnosed or declared', which explored the barriers to support due to the person's ID not being identified by others or disclosed by the person; 'It will crumble men', which reported on the additional challenges faced by homeless people with ID; 'disabling environment' which identified the ways in which organisations can make support difficult for people with ID to access; and 'It's not against them, it's to help them' which explored the benefits and issues associated with screening for ID in homeless services. The results identified the complex support needs likely to be experienced by many homeless people with ID and suggested a number of implications for practice. First, the screening tool was seen as having a number of benefits, if used where there is a process to provide the person with further specialist assessment and support. Second, staff members identified a need for training in relation to identifying and supporting this group of people. Third, the screening tool was seen as a way to help provide information about the prevalence and needs of people with ID, in order to inform and shape policy, service development, and delivery.